Proximity-activated DNA scanning encoded sequencing for massive access to membrane proteins nanoscale organization - Xueqi Zhao; Yue Zhao; Zhu Li; Huan Liu; Wenhao Fu; Feng Chen; Ying Sun; Daqian Song; Chunhai Fan; Yongxi Zhao (Proceedings of the National Academy of Sciences, 2025)
Cellular structure maintenance and function regulation critically depend on the composition and spatial distribution of numerous membrane proteins. However, current methods face limitations in spatial coverage and data scalability, hindering the comprehensive analysis of protein interactions in complex cellular nanoenvironment. Herein, we introduce p roximity- a ctivated D NA s canning e ncoded sequencing (PADSE-seq), an innovative technique that utilizes flexible DNA probes with adjustable lengths. These dynamic probes are anchored at a single end, enabling free swings within a nanoscale range to perform global scanning, recording, and accumulating of information on diverse proximal proteins in random directions along unrestricted paths. PADSE-seq leverages the autonomous cyclic cleavage of single-stranded DNA to sequentially activate encoded probes distributed throughout the local area. This process triggers strand displacement amplification and bidirectional extension reactions, linking proteins barcodes with molecular barcodes in tandem and further generating millions to billions of amplicons embedded with the combinatorial identifiers for next-generation sequencing analysis. As a proof of concept, we validated PADSE-seq for mapping the distribution of over a dozen kinds of proteins, including HER1, EpCAM, and PDL1, in proximity to HER2 in breast cancer cell lines, demonstrating its ability to decode multiplexed protein proximities at the nanoscale. Notably, we observed that the spatial distribution of proximal proteins around low-abundance target proteins exhibited greater diversity across regions with variable proximity ranges. This method offers a massive access for high-resolution and comprehensive mapping of cellular molecular interactions, paving the way for deeper insights into complex biological processes and advancing the field of precision medicine.